Anticorrosive properties of polypyrrole films modified with zinc onto SAE 4140 steel - Lehr, Ivana Leticia (2013)
Polypyrrole (PPy) films modified with zinc were electrosynthesized onto SAE 4140 steel in presence of bis(2-ethylhexyl) sulfosuccinate (AOT). The Zn and PPy electrodeposition was realized by using cyclic voltammetry at different temperatures. The corrosion protection properties of the films were examined in chloride solution by open circuit measurements, linear polarization and electrochemical impedance spectroscopy (EIS). The obtained results indicate that the presence of Zn in the polymer matrix improves the anticorrosive performance of PPy films. The best anticorrosion efficiency was obtained for the coatings modified at 20 °C which provided anodic protection to the steel substrate for a long period of immersion in chloride solution. Cathodic protection was observed when the electrodeposition temperature was increased. Adherence and anticorrosive properties declined sharply for the coatings electrosynthesized at 5 °C.